Wax removal in textile manufacturing wastewater using surface modification of rice straw - Wong, Yee Ching; Abdullah, Nur Atiqah; Yap, Taufiq Yun Hin; Ibrahim, Noor Azlina (Planetary Scientific Research Center, 2012)
In this study, the effect of modification surface on lignocellulosic adsorbent (rice straws) was developed and examined. The surface of lignocellulosic adsorbent was treated with Cetylpyridinium chloride (CPC) solution, sodium hydroxide (NaOH) solution and mixture of NaOH and CPC solution at 90 ± 5°C with different chemical treatments method. The surface morphologies of treated and untreated rice straws were observed by Scanning Electron Microscope (SEM). The treated rice straws adsorb more wax compared to untreated rice straws.